2013
DOI: 10.1371/journal.pgen.1003870
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Binding to Elk-1 by SLE-Associated IL10 Risk Allele Upregulates IL10 Expression

Abstract: Immunoregulatory cytokine interleukin-10 (IL-10) is elevated in sera from patients with systemic lupus erythematosus (SLE) correlating with disease activity. The established association of IL10 with SLE and other autoimmune diseases led us to fine map causal variant(s) and to explore underlying mechanisms. We assessed 19 tag SNPs, covering the IL10 gene cluster including IL19, IL20 and IL24, for association with SLE in 15,533 case and control subjects from four ancestries. The previously reported IL10 variant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…One previous study showed that serum IL-10 levels were positively correlated with the presence in serum of RF and anti-CCP antibodies in RA patients 24. Similar studies have also been conducted in other autoimmune diseases such as systemic lupus erythematosus (SLE),28 29 and showed that serum IL-10 levels in SLE patients were positively related to increased disease activity 30. Interindividual variability in IL-10 expression is affected by genetic variance, and so IL-10 gene polymorphisms might affect its expression and activity, and thereby influence RA pathogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…One previous study showed that serum IL-10 levels were positively correlated with the presence in serum of RF and anti-CCP antibodies in RA patients 24. Similar studies have also been conducted in other autoimmune diseases such as systemic lupus erythematosus (SLE),28 29 and showed that serum IL-10 levels in SLE patients were positively related to increased disease activity 30. Interindividual variability in IL-10 expression is affected by genetic variance, and so IL-10 gene polymorphisms might affect its expression and activity, and thereby influence RA pathogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…SNP genotypes that met the quality control criteria8 were included for association tests. Subjects with missing genotype rates >10% shared identity by descent >0.4, gender mismatch or genetic outliers (estimated using principal components analysis and ADMIXMAP9 10) were removed, resulting in 15 292 unrelated subjects with clean data.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has identified an IL10 upstream SNP that tags a risk haplotype associated with SLE in European population [36 ▪▪ ]. The SLE-risk allele is associated with increased IL10 expression by preferentially binds to the phosphorylated transcription factor Elk-1.…”
Section: Sle Susceptibility Genes Stratified By Biological Pathwaysmentioning
confidence: 99%